Severe Developmental B Lymphopoietic Defects in Foxp3-Deficient Mice are Refractory to Adoptive Regulatory T Cell Therapy - Riewaldt, Julia; Düber, Sandra; Boernert, Marie; Dembinski, Marcin; Weiss, Siggi; Garbe, Annette I.; Kretschmer, Karsten (Frontiers in Immunology, 2012)
The role of Foxp3-expressing regulatory T (Treg) cells in tolerance and autoimmunity is well established. However, although of considerable clinical interest, the role of Treg cells in the regulation of hematopoietic homeostasis remains poorly understood. Thus, we analysed B and T lymphopoiesis in the scurfy (Sf) mouse model of Treg cell deficiency. In these experiments, the near-complete block of B lymphopoiesis in the BM of adolescent Sf mice was attributed to autoimmune T cells. We could exclude a constitutive lympho-hematopoietic defect or a B cell-intrinsic function of Foxp3. Efficient B cell development in the BM early in ontogeny and pronounced extramedullary B lymphopoietic activity resulted in a peripheral pool of mature B cells in adolescent Sf mice. However, marginal zone B and B-1a cells were absent throughout ontogeny. Developmental B lymphopoietic defects largely correlated with defective thymopoiesis. Importantly, neonatal adoptive Treg cell therapy suppressed exacerbated production of inflammatory cytokines and restored thymopoiesis but was ineffective in recovering defective B lymphopoiesis, probably due to a failure to compensate production of stroma cell-derived IL-7 and CXCL12. Our observations on autoimmune-mediated incapacitation of the BM environment in Foxp3-deficient mice will have direct implications for the rational design of BM transplantation protocols for patients with severe genetic deficiencies in functional Foxp3+ Treg cells.